Geosurveillance, Location Privacy, and Personalization. (October 2019) - Banerjee, Syagnik
As connected consumers expand their digital footprint, firms are legally purchasing location data generated by apps, sold to intermediaries, and cleaned by analytics vendors for personalized targeting, advertising, and risk profiling. Data storage and flow across multiple sectors and states cause increased variability in agency jurisdiction, legal standards, and premise for legal recourse to privacy violations. To better inform industries, policy makers, and consumers in this rapidly changing environment, the author develops a new construct, location privacy, articulating the rich impact of geosurveillance on the consumer. Analysis of studies conducted using car GPS and wearable devices find that data service provider familiarity (known, unknown) and georeferencing style (environment, movement) affect location privacy concerns and the adoption likelihood of personalized driving and health insurance policies underwritten with disclosed location data. The article discusses implications about potential marketer liabilities and regulators' roles in moderating the market's concerns regarding geosurveillance.